Aluminum-based fin material
Patent Information
- Application Number
- JP2023130114
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-08-09
- Publication Date
- 2025-02-21
AI Technical Summary
【0011】 本発明に係るアルミニウム製フィン材は、アルミニウム製フィン材としての従来の機能を損なうことなく、抗ウイルス·抗菌性も備える。そのため、親水性皮膜層による親水性や、アルミニウム製フィン材としての成形性を維持しつつ、室内空間中に存在するウイルス·細菌を好適に低減できる。
Smart Images

Figure 2025025390000001
Abstract
Description
[Technical field]
[0001] The present invention relates to an aluminum fin material. [Background technology]
[0002] Heat exchangers are used in a variety of products, including room air conditioners, packaged air conditioners, freezer showcases, refrigerators, oil coolers, radiators, etc. Aluminum and aluminum alloys, which have excellent thermal conductivity, workability, and corrosion resistance, are commonly used as materials for heat exchanger fins.
[0003] There is a demand for room air conditioners and other products to have antiviral and antibacterial properties to prevent infection by viruses and bacteria.
[0004] Viruses and bacteria are contained in the airborne particles expelled when an infected person sneezes, etc., and it is believed that viral and bacterial infections occur when the airborne particles are directly inhaled or when the infected person comes into contact with something that has the particles on it. In contrast, when the air conditioner is turned on and the air in the room is circulated, the viruses and bacteria floating in the indoor space are also circulated.
[0005] As a result, filters installed in the air flow path of air conditioners that have been given antiviral and antibacterial properties have been released onto the market. Specifically, Patent Document 1 discloses an air conditioner filter that includes an antiviral photocatalytic material that includes at least one type of fine particles selected from tungsten oxide fine particles and tungsten oxide composite fine particles. [Prior art documents] [Patent documents]
[0006] [Patent Document 1] JP 2011-212613 A Summary of the Invention [Problem to be solved by the invention]
[0007] However, further reduction of viruses and bacteria present in indoor spaces is desired. Therefore, the present inventors have investigated the imparting of antiviral and antibacterial properties to the heat exchangers themselves used in air conditioners, and in particular, have investigated the imparting of antiviral and antibacterial properties to aluminum fin materials.
[0008] In other words, the present invention aims to provide an aluminum fin material that has antiviral and antibacterial properties without compromising the conventional functions of aluminum fin material. [Means for solving the problem]
[0009] In response to the above problem, the present inventors have conducted further research and found that the use of inorganic antiviral and antibacterial agents reduces the formability of aluminum fin materials. In addition, it has been found that when an antiviral and antibacterial agent is contained in a corrosion-resistant coating layer, the desired hydrophilic performance cannot be obtained even if a hydrophilic coating layer is formed on the surface of the corrosion-resistant coating layer. This is believed to be because the antiviral and antibacterial agent is not compatible with the corrosion-resistant coating layer and undergoes microphase separation, resulting in a decrease in adhesion of the hydrophilic coating layer to the corrosion-resistant coating layer. As a result of further investigation, the inventors discovered that the above problems could be solved by incorporating an organic antiviral and antibacterial agent into the hydrophilic coating layer, which led to the completion of the present invention.
[0010] The present invention relates to the following [1] to [8]. [1] An aluminum plate having a corrosion-resistant coating layer and a hydrophilic coating layer in this order on at least one surface of the aluminum plate; The hydrophilic coating layer is an aluminum fin material containing a hydrophilic resin and an organic antiviral and antibacterial agent. [2] The content of the organic antiviral and antibacterial agent in the hydrophilic coating layer is 0.10 to 0.60 mg / dm 2 The aluminum fin material according to [1] above. [3] The aluminum fin material according to [1] or [2], wherein the organic antiviral and antibacterial agent includes a phenolic antiviral and antibacterial agent. [4] The aluminum fin material according to any one of [1] to [3] above, wherein the hydrophilic resin contains an acrylic resin containing a sulfonic acid group and an ether bond. [5] The aluminum fin material according to any one of [1] to [4] above, wherein the corrosion-resistant coating layer contains an epoxy resin. [6] The aluminum fin material according to any one of [1] to [5] above, further comprising a lubricating coating layer on the surface of the hydrophilic coating layer. [7] The aluminum fin material described in [6], wherein the lubricating coating layer comprises a resin matrix containing polyethylene glycol as a main component and a hydrophilic component containing at least one of a sulfonic acid group and an ester group. [8] The aluminum fin material according to any one of [1] to [7], further comprising a base treatment layer between the aluminum plate and the corrosion-resistant coating layer. Effect of the Invention
[0011] The aluminum fin material according to the present invention has antiviral and antibacterial properties without compromising the conventional functions of the aluminum fin material. Therefore, it is possible to effectively reduce viruses and bacteria present in an indoor space while maintaining the hydrophilicity of the hydrophilic coating layer and the formability of the aluminum fin material. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0012] Hereinafter, an embodiment of the aluminum fin material according to the present invention will be described in detail. Note that the symbol "to" indicating a numerical range is used to mean that the numerical range includes the numerical ranges before and after the symbol as the lower and upper limits.
[0013] Aluminum fin material The aluminum fin material (hereinafter sometimes simply referred to as "fin material") of this embodiment comprises an aluminum plate and, on at least one surface of the aluminum plate, a corrosion-resistant coating layer and a hydrophilic coating layer, in that order.
[0014] <Hydrophilic film layer> The hydrophilic coating layer in this embodiment is a coating layer that imparts hydrophilicity to the surface of the fin material, and contains a hydrophilic resin and an organic antiviral and antibacterial agent. Compared to inorganic antiviral and antibacterial agents, the use of organic antiviral and antibacterial agents can impart antiviral and antibacterial properties without reducing the formability of aluminum fin material. Furthermore, by incorporating an organic antiviral / antibacterial agent into the hydrophilic coating layer, it is possible to impart good antiviral / antibacterial properties without reducing the hydrophilic performance of the hydrophilic coating layer, unlike the case where the agent is incorporated into the corrosion-resistant coating layer.
[0015] The organic antiviral / antibacterial agent in this embodiment is not particularly limited as long as it is an organic substance that exhibits at least one of antiviral activity and antibacterial activity, and known organic substances can be used. Examples of organic antiviral and antibacterial agents include imidazoles, thiazoles, isothiazolinones, pyridines, triazines, aldehydes, phenols, piguanides, nitriles, halogens, anilides, disulfides, thiocarbamates, quaternary ammonium salts, organometallics, alcohols, carboxylic acids, and natural products. The organic antiviral / antibacterial agent may be appropriately selected from the viewpoint of solubility and dispersibility in the coating composition used to form the hydrophilic coating layer, and for example, a phenolic antiviral / antibacterial agent is preferable. In addition, only one type of antiviral / antibacterial agent may be used, or two or more types may be used in combination.
[0016] In this embodiment, the content of the organic antiviral and antibacterial agent in the hydrophilic coating layer is 0.10 mg / dm 2 More than 0.10 to 0.60 mg / dm 2Here, from the viewpoint of realizing better antiviral and antibacterial properties, the above content is more preferably 0.10 mg / dm 2 More than 0.15 mg / dm 2 More preferably, 0.20 mg / dm 2 On the other hand, the above content is more preferable from the viewpoint that excessive addition is unnecessary because the antiviral and antibacterial performance reaches a plateau, and from the viewpoint of not excessively impairing the function of each coating layer constituting the fin material, the above content is 0.60 mg / dm 2 Less than 0.50 mg / dm 2 Less than 0.40 mg / dm is more preferable. 2 The following is even more preferred:
[0017] The hydrophilic resin contained in the hydrophilic coating layer in this embodiment may be any hydrophilic resin known in the art. The hydrophilic resin may contain one type of resin or two or more types of resins as long as it has a hydrophilic group. Examples of the hydrophilic group include a hydroxyl group, a carboxyl group, a sulfonic acid group, and a polyether group.
[0018] Examples of hydrophilic resins having a hydroxyl group include polyethylene glycol (PEG) and polyvinyl alcohol (PVA). An example of a hydrophilic resin having a carboxyl group is polyacrylic acid (PAA). An example of a hydrophilic resin having a hydroxyl group and a carboxyl group is carboxymethyl cellulose (CMC). An example of a hydrophilic resin having a sulfonic acid group is sulfoethyl acrylate. Examples of hydrophilic resins having a polyether group include polyethylene glycol (PEG) and modified compounds thereof.
[0019] Among these, from the viewpoint of more suitably expressing the desired hydrophilicity even when a lubricating coating layer is formed on the surface of the hydrophilic coating layer, the hydrophilic resin is preferably one containing a sulfonic acid group or a polyether group, i.e., one containing an ether bond, more preferably one containing a sulfonic acid group and an ether bond, and particularly preferably an acrylic acid resin containing a sulfonic acid group and an ether bond.
[0020] The acrylic acid resin containing sulfonic acid and ether bonds is an acrylic acid resin containing an unsaturated double bond group and a sulfonic acid group, and is typically 3-allyloxy-2-hydroxy-1-propanesulfonic acid sodium salt (HAPS), but other examples include acrylamidomethylpropanesulfonic acid, etc. The acrylic acid resin containing sulfonic acid and ether bonds is not limited to these.
[0021] In addition to the above, the hydrophilic resin may be a copolymer of two or more monomers having a hydrophilic group. For example, a copolymer of acrylic acid and sulfoethyl acrylate may be used. The copolymer may be an alternating copolymer, a block copolymer, a graft copolymer, a random copolymer, or the like, and the arrangement of the monomers is not particularly limited.
[0022] The hydrophilic coating layer preferably contains a surfactant in addition to the hydrophilic resin. In this way, when a lubricating coating layer is formed on the hydrophilic coating layer, the lubricating coating layer can provide both processability and better hydrophilicity. This is believed to be due to the exposure effect of the surfactant.
[0023] The surfactant may be any of anionic, cationic, and nonionic surfactants, but anionic surfactants are preferred from the viewpoint of ease of dispersion in the hydrophilic coating layer. One type of surfactant may be used, or two or more types may be used in combination.
[0024] Examples of the anionic surfactant include polyoxyethylene alkyl ether phosphate, polyoxyethylene alkyl ether sulfate, and polyoxyethylene alkyl sulfosuccinate.
[0025] Examples of nonionic surfactants include ethylenediamine polyoxypropylene-polyoxyethylene condensates, polyoxyethylene sorbitan monolaurate, polyoxyethylene polyoxypropylene block polymers, polyoxyethylene sorbitan monostearate, and the like.
[0026] In addition to the hydrophilic resin and surfactant, the hydrophilic coating layer may contain other optional components within the range that does not impair the effects of the present invention. Examples of the optional components include various paint additives for improving the physical properties of the coating layer.
[0027] Examples of paint additives include crosslinking agents, surface conditioners, wetting and dispersing agents, antisettling agents, antioxidants, defoamers, rust inhibitors, etc. These paint additives may be contained alone or in combination of two or more.
[0028] The coating amount of the hydrophilic coating layer in this embodiment is 0.1 to 28 mg / dm 2 Here, from the viewpoint of obtaining better hydrophilicity, the coating amount of the hydrophilic coating layer is preferably 0.1 mg / dm 2 More than 0.3 mg / dm 2 More preferably, 0.5 mg / dm 2 More preferably, the amount of the hydrophilic coating layer is 28 mg / dm2 or more, from the viewpoint of obtaining good coating workability when forming the hydrophilic coating layer, and from the viewpoint of obtaining good functions of the corrosion-resistant coating layer formed on the aluminum plate side of the hydrophilic coating layer. 2 Less than 25 mg / dm 2 The following is more preferred: The coating weight of the hydrophilic coating layer can be measured by known methods such as fluorescent X-rays, an infrared coating thickness meter, weight measurement by coating peeling, etc. The same applies to the coating weights of each coating layer other than the hydrophilic coating layer.
[0029] The amount of hydrophilic resin attached to the hydrophilic coating layer is 0.05 to 5 g / m 2Here, from the viewpoint of obtaining sufficient hydrophilicity, the coating amount is preferably 0.05 g / m 2 More than 0.1 g / m is preferable. 2 More preferably, 0.3 g / m or more 2 The above-mentioned adhesion amount is more preferably 5 g / m from the viewpoint of preventing the hydrophilic resin from eluting when the surface of the fin material becomes wet with water and impairing the oil repellency of the functional film. 2 Less than 1 g / m is preferable. 2 Less than 0.8 g / m is more preferable. 2 The following is even more preferred:
[0030] When the hydrophilic film contains a surfactant, the amount of the surfactant attached to the hydrophilic film is 0.0003 to 0.7 g / m 2 Here, from the viewpoint of obtaining sufficient hydrophilicity, the adhesion amount is preferably 0.0003 g / m 2 More than 0.0005 g / m is preferable. 2 More preferably, 0.001 g / m or more 2 Furthermore, in the case where the hydrophilicity is too strong and a lubricating coating layer is provided on the hydrophilic coating layer, the coating amount is preferably 0.7 g / m from the viewpoint of preventing the lubricity of the lubricating coating layer from being hindered. 2 Less than 0.5 g / m is preferred. 2 Less than 0.05 g / m is more preferable. 2 The following is even more preferred:
[0031] The amount and thickness of the hydrophilic coating layer can be adjusted by the concentration of the coating composition used to form the hydrophilic coating layer, the selection of the bar coater number, and the like.
[0032] <Corrosion-resistant coating layer> The fin material according to this embodiment includes a corrosion-resistant coating layer between the aluminum plate and the hydrophilic coating layer. The corrosion-resistant coating layer is a layer formed on the aluminum plate mainly to enhance the corrosion resistance of the aluminum plate.
[0033] When a base treatment layer described later is formed on the surface of the aluminum plate, the corrosion-resistant coating layer is preferably provided between the base treatment layer and the hydrophilic coating layer. In addition, when a coating layer having another function such as an anti-frost coating layer is formed on the aluminum plate or on the base treatment layer, the corrosion-resistant coating layer may be formed on the coating layer.
[0034] The corrosion-resistant coating layer preferably contains a hydrophobic resin, and can be formed, for example, by applying a coating composition containing a hydrophobic resin onto an aluminum plate, an undercoat treatment layer, or a coating layer such as an anti-frost coating layer, and then solidifying it by drying or the like.
[0035] The corrosion-resistant coating layer makes it difficult for moisture such as condensation water, oxygen, chloride ions and other ionic species to penetrate the aluminum plate, thereby suppressing corrosion of the aluminum plate and the production of odorous aluminum oxides.
[0036] The hydrophobic resin in the corrosion-resistant film layer can be a conventionally known one. For example, various resins such as polyester, polyolefin, melamine, epoxy, urethane, and acrylic resins can be used, and one or a mixture of two or more of these can be used. For example, from the viewpoint of obtaining better corrosion resistance, the corrosion-resistant film layer in this embodiment preferably contains an epoxy resin.
[0037] In addition to the hydrophobic resin, the corrosion-resistant coating layer may contain other optional components within the range that does not impair the effects of the present invention. Examples of the optional components include various water-based solvents and paint additives for improving the paintability, workability, and physical properties of the coating.
[0038] Examples of paint additives include water-soluble organic solvents, crosslinking agents, surfactants, surface conditioners, wetting and dispersing agents, anti-settling agents, antioxidants, defoamers, rust inhibitors, etc. These paint additives may be contained alone or in combination of two or more.
[0039] The amount of the corrosion-resistant coating layer is not particularly limited, but is preferably 3 to 60 mg / dm 2Here, from the viewpoint of imparting sufficient corrosion resistance to the aluminum plate, the coating amount of the corrosion-resistant coating layer is preferably 3 mg / dm 2 On the other hand, even if the coating amount of the corrosion-resistant coating layer is increased, the obtained corrosion resistance effect reaches a plateau, and from the viewpoint of suppressing the decrease in the heat exchange efficiency of the fin material, the coating amount of the corrosion-resistant coating layer is preferably 60 mg / dm 2 The following is preferred: The coating weight of the corrosion-resistant coating layer can be adjusted by the concentration of the coating composition used to form the corrosion-resistant coating layer, the selection of the bar coater number, and the like.
[0040] <Lubricating film layer> The aluminum fin material according to this embodiment preferably further comprises a lubricating coating layer on the surface of the hydrophilic coating layer. The lubricating coating layer is a layer that enhances the lubricity of the fin material surface. This reduces the friction coefficient of the fin material and improves the processability, such as press formability, when processing the fin material into a fin. It is more preferable that the lubricating coating layer be the outermost layer of the aluminum fin material.
[0041] The lubricating coating layer in this embodiment preferably contains a resin matrix and a hydrophilic component. Here, the resin matrix means a resin component that is a base composition for forming the lubricating coating layer. The content of the resin matrix is preferably 60% by mass or more based on the total amount of components constituting the lubricating coating layer. In addition, from the viewpoint of fully exerting the functions of the components other than the resin matrix, the content is preferably 70% by mass or less.
[0042] The resin matrix in this embodiment preferably contains polyethylene glycol (PEG) as a main component, from the viewpoint of suppressing deterioration of hydrophilic performance due to heat and obtaining good heat resistance when combined with a specific hydrophilic component described later. Here, the main component of the resin matrix means that the content thereof is 60 mass % or more with respect to the total resins constituting the resin matrix.
[0043] The polyethylene glycol mentioned above also includes modified compounds thereof. The modified polyethylene glycol compound may be a modified polyethylene glycol having in its structure a functional group having one or more bonds selected from the group consisting of a urethane bond, an ester bond, and an ether bond. Among these, a modified polyethylene glycol having in its structure a functional group having a urethane bond is preferred in terms of having a functional group with excellent elongation.
[0044] Furthermore, when the resin matrix contains two or more types of polyethylene glycols with different molecular weights or structures, if the total amount of these is 60 mass % or more, it can be said that the resin matrix contains polyethylene glycol as a main component.
[0045] In the resin matrix of this embodiment, the content of polyethylene glycol, which is the main component, is preferably 60% by mass or more, more preferably 70% by mass or more, even more preferably 80% by mass or more, and may be 100% by mass, i.e., the resin matrix may consist only of polyethylene glycol.
[0046] In the case where the resin matrix in this embodiment contains a resin other than polyethylene glycol, the other resin may be, for example, a resin having a hydrophilic group, such as a hydroxyl group, a carboxyl group, a sulfonic acid group, or a polyether group.
[0047] Examples of resins having a hydroxyl group other than polyethylene glycol (PEG) include polyvinyl alcohol (PVA). An example of a material having a carboxyl group is polyacrylic acid (PAA). An example of a material having a hydroxyl group and a carboxyl group is carboxymethyl cellulose (CMC). An example of a compound having a sulfonic acid group is sulfoethyl acrylate. In addition to these, copolymers of two or more kinds of monomers having a hydrophilic group can also be used.
[0048] The hydrophilic component in this embodiment is preferably a component containing at least one of a sulfonic acid group and an ester group, and more preferably one in which the amount of functional groups contributing to hydrophilicity changes by 15% or less before and after heating for 10 minutes at 200° C. This allows the hydrophilic effect of the hydrophilic coating layer to be maintained without being lost due to heating or the like, and realizes hydrophilicity with excellent heat resistance.
[0049] Examples of hydrophilic components containing at least one of a sulfonic acid group and an ester group include sulfonic acid acrylic compounds, phosphate ester compounds, acrylic compounds, etc. It is more preferable that these compounds have a change in the amount of functional groups contributing to hydrophilicity of 15% or less before and after heating at 200° C. for 10 minutes.
[0050] The change in the amount of functional groups that contribute to hydrophilicity of the hydrophilic component before and after heating at 200° C. for 10 minutes is preferably 15% or less, more preferably 10% or less, and even more preferably 5% or less. In this specification, the change in the amount of functional groups that contribute to hydrophilicity can be measured using a Fourier transform infrared spectrophotometer.
[0051] In this embodiment, the content of the hydrophilic component relative to 100 parts by mass of the resin matrix is preferably 2.0 to 6000 parts by mass. From the viewpoint of obtaining high hydrophilicity, the content is preferably 2.0 parts by mass or more, more preferably 5.0 parts by mass or more, even more preferably 6.0 parts by mass or more, even more preferably 8.0 parts by mass or more, and particularly preferably 10 parts by mass or more. On the other hand, from the viewpoint of obtaining good processability, the content is preferably 6000 parts by mass or less, more preferably 5000 parts by mass or less, even more preferably 4000 parts by mass or less, and particularly preferably 3000 parts by mass or less. In this way, by setting the content of the hydrophilic component in the resin matrix within an appropriate range, it is possible to achieve and improve both good processability and properties such as hydrophilicity related to preventing water splashing and reducing ventilation resistance without interfering with each other.
[0052] A preferred combination of a resin matrix and a hydrophilic component in the lubricating coating layer in this embodiment is a resin matrix containing polyethylene glycol as a main component, and a hydrophilic component containing at least one of a sulfonic acid group and an ester group. More preferred combinations are those in which the preferred embodiments of the polyethylene glycol and the hydrophilic component described above can be used in any combination.
[0053] In addition to the resin matrix and hydrophilic component, the lubricating coating layer of this embodiment may contain other optional components, such as various paint additives for improving desired physical properties, as long as the optional components do not impair the effects of the present invention.
[0054] Examples of paint additives include crosslinkers, surfactants, surface conditioners, wetting and dispersing agents, antisettling agents, antioxidants, defoamers, antifouling agents, rust inhibitors, etc. These paint additives may be contained alone or in combination of two or more.
[0055] The coating amount of the lubricating coating layer in this embodiment is 0.05 to 3.0 mg / dm 2 Here, from the viewpoint of obtaining sufficient corrosion resistance and heat-resistant hydrophilicity, the coating amount is preferably 0.05 mg / dm 2 More than 0.1 mg / dm 2 More preferably, 0.2 mg / dm 2 On the other hand, from the viewpoint of suppressing a decrease in hydrophilicity due to a part of the components constituting the lubricating coating layer remaining on the surface when the surface of the fin material is wetted with water, the above coating amount is 3.0 mg / dm 2 Less than 1.5 mg / dm 2 Less than 1.0 mg / dm is more preferable. 2 The following is even more preferred:
[0056] The coating weight of the lubricating coating layer can be adjusted by the concentration of the coating composition used to form the lubricating coating layer, the selection of the bar coater number, and the like.
[0057] In the aluminum fin material according to this embodiment, the total thickness of the corrosion-resistant coating layer, the hydrophilic coating layer, and the lubricating coating layer is preferably 5 μm or less in order to prevent a decrease in the heat exchange efficiency of the fin material.
[0058] <Aluminum plate> The aluminum plate in this embodiment is a concept that includes a plate made of aluminum and a plate made of an aluminum alloy, and an aluminum plate that has conventionally been used for aluminum fin materials can be used.
[0059] As the aluminum plate, 1000 series aluminum as specified in JIS H 4000:2014 is preferable because of its excellent thermal conductivity and workability. More specifically, aluminum alloy numbers 1050, 1070, and 1200 are more preferable as the aluminum plate. However, the above description does not exclude the use of 2000 series to 9000 series aluminum alloys or other aluminum plates as the aluminum plate.
[0060] The aluminum plate is cut to a desired thickness depending on the application and specifications of the fin material. The fin material for heat exchangers preferably has a thickness of 0.08 to 0.3 mm. From the viewpoint of the strength of the fin, the thickness of the fin material is preferably 0.08 mm or more, and more preferably 0.1 mm or more. On the other hand, from the viewpoint of the workability into the fin and the heat exchange efficiency, the thickness of the fin material is preferably 0.3 mm or less, and more preferably 0.2 mm or less.
[0061] At least a corrosion-resistant coating layer and a hydrophilic coating layer are provided in this order on at least one surface of the aluminum plate, but at least a corrosion-resistant coating layer and a hydrophilic coating layer may be provided in this order on both surfaces. In addition, when a corrosion-resistant coating layer and a hydrophilic coating layer are provided on both surfaces, the configurations of the coating layers on both surfaces do not necessarily have to be the same.
[0062] <Base treatment layer> The aluminum fin material according to this embodiment may further include a base treatment layer between the aluminum plate and the corrosion-resistant coating layer. By providing the undercoat treatment layer, the corrosion resistance of the aluminum plate can be improved, and also the adhesion between the aluminum plate and the corrosion-resistant coating layer can be improved.
[0063] The undercoat treatment layer in this embodiment may be any known layer capable of imparting corrosion resistance to the aluminum plate, for example, a layer made of an inorganic oxide or an inorganic-organic composite compound. Examples of inorganic materials that form inorganic oxides and inorganic-organic composite compounds include chromium (Cr), zirconium (Zr), and titanium (Ti).
[0064] The layer made of an inorganic oxide that serves as the undercoat treatment layer can be formed, for example, by subjecting an aluminum plate to a chromate phosphate treatment, a zirconium phosphate treatment, a zirconium oxide treatment, a chromate chromate treatment, a zinc phosphate treatment, a titanic acid phosphate treatment, etc. However, the type of inorganic oxide is not limited to those formed by these treatments.
[0065] The layer made of an inorganic-organic composite compound that serves as the undercoat treatment layer can be formed, for example, by subjecting an aluminum plate to coating-type chromate treatment, coating-type zirconium treatment, etc. Specific examples of such inorganic-organic composite compounds include, for example, acrylic-zirconium composites.
[0066] The thickness of the undercoat treatment layer is not particularly limited and may be set appropriately, but the amount of the coating per unit area should be 1 to 100 mg / m2 in terms of metal (Cr, Zr, Ti). 2 The thickness of the film is preferably 1 to 100 nm.
[0067] The coating amount and film thickness of the undercoat treatment layer can be adjusted by the concentration of the chemical conversion treatment solution used in forming the undercoat treatment layer, the film formation treatment time, and the like.
[0068] <Characteristics of aluminum fin material> The aluminum fin material according to this embodiment has antiviral and antibacterial properties without impairing the conventional functions of the fin material. Specifically, it can achieve good antiviral and antibacterial performance without impairing formability or hydrophilicity.
[0069] Of the above, formability was verified when organic antiviral / antibacterial agents and inorganic antiviral / antibacterial agents were used; however, when inorganic antiviral / antibacterial agents were used, it was necessary to increase the amount added to the coating in order to express antiviral / antibacterial properties, which resulted in a decrease in hydrophilicity.
[0070] Furthermore, when considering that the aluminum fin material is to be used in, for example, a heat exchanger, it is necessary for the aluminum fin material to maintain hydrophilicity at least to the same degree as conventional materials. Specifically, it can be said that a contact angle of the droplet before repeated immersion and drying, as measured by the method described in the Examples described later, is good if it is 18° or less, preferably 16° or less, more preferably 13° or less, and even more preferably 11° or less, and the smaller the angle, the better. In addition, if the contact angle of the droplet after 14 cycles of immersion and drying is 20° or less, it can be evaluated that good hydrophilicity has been achieved with durability equal to or greater than that of conventional methods, and the above contact angle is more preferably 19° or less, even more preferably 18° or less, and the smaller the contact angle, the more preferable.
[0071] The antiviral and antibacterial properties of aluminum fin material can be evaluated through tests for SIAA mark certification. Specifically, antiviral tests are conducted in accordance with ISO 21702, and antibacterial tests are conducted in accordance with JIS Z 2801:2012, using test specimens that have been treated with a water resistance test or a light resistance test. Regardless of whether the product has been subjected to a water resistance test or a light resistance test, if the antiviral activity value is 2.0 or higher, it can be judged to have antiviral effectiveness. Additionally, regardless of whether the product has been subjected to a water resistance test or a light resistance test, if the antibacterial activity value is 2.0 or higher, it can be judged to have antibacterial effectiveness.
[0072] <<Method for manufacturing aluminum fin material>> The aluminum fin material according to this embodiment can be manufactured by sequentially forming a corrosion-resistant coating layer and a hydrophilic coating layer on at least one surface of an aluminum plate. The coating composition used in the step of forming the hydrophilic coating layer contains a hydrophilic resin and an organic antiviral and antibacterial agent.
[0073] Hereinafter, one embodiment of the manufacturing method of the aluminum fin material according to the present embodiment will be specifically described. In the following, a base treatment layer, a corrosion-resistant film layer, a hydrophilic film layer, and a lubricating film layer are formed on the surface of the aluminum plate in this order, but the formation of the base treatment layer and the lubricating film layer is optional. In addition, a film layer having another function may be further provided.
[0074] When forming a base treatment layer on the surface of an aluminum plate, a conventionally known method can be adopted. Specifically, when the base treatment layer is a layer made of an inorganic oxide, for example, the base treatment layer can be formed by subjecting the aluminum plate to a chromate phosphate treatment, a zirconium phosphate treatment, a zirconium oxide treatment, a chromate chromate treatment, a zinc phosphate treatment, a titanic acid phosphate treatment, or the like. When the undercoat treatment layer is a layer made of an inorganic-organic composite compound, the undercoat treatment layer can be formed, for example, by subjecting the aluminum plate to a coating type chromate treatment or a coating type zirconium treatment.
[0075] Before forming the primer layer, the surface of the aluminum plate may be degreased in advance using an alkaline degreasing solution, which improves the reactivity of the primer treatment and also improves the adhesion of the formed primer layer.
[0076] Next, in the step of forming a corrosion-resistant coating layer, a coating composition containing a material for enhancing the corrosion resistance of the aluminum plate, such as a hydrophobic resin or a precursor thereof, is applied to the surface of the base treatment layer, and dehydration condensation is carried out. This forms a corrosion-resistant coating layer. The hydrophobic resin is as described above, and an example of the hydrophobic resin is an epoxy resin.
[0077] The above coating composition may further contain an aqueous solvent, a water-soluble organic solvent, the above-mentioned coating additives, etc., from the viewpoint of improving the coatability, workability, physical properties of the coating, etc.
[0078] The reaction temperature and reaction time in the dehydration condensation reaction are not particularly limited, and conventionally known conditions may be adopted.
[0079] In the step of forming the corrosion-resistant coating layer, drying may be carried out as necessary after the above-mentioned dehydration condensation.
[0080] The hydrophilic coating layer can be formed by applying a coating composition containing a hydrophilic resin and an organic antiviral / antibacterial agent onto the corrosion-resistant coating layer and solidifying it by drying or the like. The hydrophilic resin and the organic antiviral / antibacterial agent can be those mentioned above, and for example, the hydrophilic resin can be an acrylic resin containing a sulfonic acid group and an ether bond. In addition, the organic antiviral / antibacterial agent can be a phenol-based antiviral / antibacterial agent.
[0081] The above coating composition may further contain an aqueous solvent, a water-soluble organic solvent, the above-mentioned coating additives, etc., from the viewpoint of improving the coatability, workability, physical properties of the coating, etc.
[0082] The lubricating coating layer can be formed by applying a coating composition containing a resin that enhances lubricity, for example, a coating composition containing a resin matrix and a hydrophilic component, onto the hydrophilic coating layer and solidifying it by drying or the like. The resin matrix and the hydrophilic component can be those described above, and for example, the resin matrix can be one containing polyethylene glycol as the main component. In addition, the hydrophilic component can be one containing at least one of a sulfonic acid group and an ester group.
[0083] The above coating composition may further contain an aqueous solvent, a water-soluble organic solvent, the above-mentioned coating additives, etc., from the viewpoint of improving the coatability, workability, physical properties of the coating, etc.
[0084] The solidification may be performed by baking. The baking temperature is not particularly limited as long as the lubricating coating layer does not peel off, but is preferably, for example, 100 to 250° C. Here, the above temperature is preferably 100° C. or higher, and more preferably 150° C. or higher. Moreover, from the viewpoint of preventing oxidation of the resin of the lubricating coating layer, the above temperature is preferably 250° C. or lower, and more preferably 200° C. or lower. The above baking temperature is the temperature of the oven in which baking is performed.
[0085] The baking time is not particularly limited as long as the lubricating coating layer does not peel off, but is preferably, for example, 3 to 30 seconds. Here, the time is preferably 3 seconds or more, more preferably 5 seconds or more. Moreover, from the viewpoint of preventing oxidation of the resin of the lubricating coating layer, the time is preferably 30 seconds or less, more preferably 20 seconds or less. EXAMPLES
[0086] The present invention will be described in more detail below with reference to examples and comparative examples. However, the present invention is not limited to these examples, and can be practiced with modifications within the scope of the invention, all of which are included in the technical scope of the present invention.
[0087] Examples 1 to 3 The aluminum plate used was an aluminum plate having a thickness of 0.1 mm and conforming to the alloy number 1070 standard specified in JIS H 4000: 2014. A primer layer was formed on one surface of the aluminum plate by phosphate chromate treatment.
[0088] Next, a coating composition was prepared by dispersing an epoxy resin composition (EPICLON (registered trademark) 840, manufactured by DIC Corporation) in water, and the coating amount was 7.5 mg / dm 2 The coating was applied to the surface of the undercoat treatment layer using a bar coater so as to obtain the coating composition shown in Table 1, and then subjected to dehydration condensation at 200° C. for 15 seconds, followed by drying to form a corrosion-resistant coating layer.
[0089] Next, a coating composition was prepared by dispersing an acrylic resin containing a sulfonic acid group and an ether bond, and a phenolic compound having antiviral and antibacterial properties in water, and the coating amount was 4.0 mg / dm 2 The hydrophilic coating layer was formed by applying the above-mentioned solution to the surface of the corrosion-resistant coating layer using a bar coater and drying the solution so as to obtain a hydrophilic coating layer. The content of the phenol-based compound in the hydrophilic coating layer in each of Examples 1 to 3 is as shown in Table 1.
[0090] Finally, a coating composition was prepared by dispersing polyethylene glycol (PEG6000, manufactured by Sanyo Chemical Industries, Ltd.) in water, and the coating amount was adjusted to 1.0 mg / dm 2 After drying, the coating was baked at 150° C. for 15 seconds to form a lubricating coating layer. In this manner, an aluminum fin material was obtained.
[0091] Comparative Examples 1 to 3 Aluminum fin materials were obtained in the same manner as in Examples 1 to 3, except that the phenolic compound having antiviral and antibacterial properties was contained in the corrosion-resistant coating layer, not in the hydrophilic coating layer, at the content shown in Table 1.
[0092] Comparative Example 4 An aluminum fin material was obtained in the same manner as in Comparative Example 2, except that a triazine-based compound having antiviral and antibacterial properties was used instead of the phenol-based compound having antiviral and antibacterial properties.
[0093] 《Reference example 1》 An aluminum fin material was obtained in the same manner as in Example 1, except that neither the corrosion-resistant coating layer nor the hydrophilic coating layer contained a compound having antiviral and antibacterial properties.
[0094] "evaluation" <Anti-viral and anti-bacterial properties> A 5cm x 5cm sample was cut out from each of the obtained aluminum fin materials. Then, each sample was subjected to a water resistance test or a light resistance test in accordance with the durability test method in the SIAA mark certification to prepare a test piece. The water resistance test was classified as 2, and the light resistance test was classified as 1.
[0095] Antiviral test (ISO 21702) A test piece measuring 5 cm x 5 cm was cut out from each of the obtained aluminum fin materials. 0.4 mL of the test virus liquid (influenza virus) was inoculated into the test piece, and the test piece was covered with a coating film. After inoculation with the test virus liquid, the test piece was left to stand at 25±1°C and 90% RH or higher for 24 hours, and then the virus infectivity (PFU / cm) was measured by the plaque method. 2 The above measurement was performed once for each aluminum fin material, and the average value was taken as the virus infectivity titer. The average viral infectivity of Reference Example 1 was designated Ut, the average viral infectivity of the Examples or Comparative Examples was designated At, and the value represented by (Ut-At) was calculated as the antiviral activity value Rt for the corresponding Example or Comparative Example. The results are shown in Table 1, and if the antiviral activity value is 2.0 or more in both the treatment by the water resistance test (after water resistance treatment) and the treatment by the light resistance test (after light resistance treatment), it can be determined that there is antiviral effectiveness. In Table 1, "-" means that it was not measured.
[0096] Antibacterial test (JIS Z 2801:2012) A test piece of 5 cm x 5 cm was cut out from each of the obtained aluminum fin materials. The above test pieces were placed in a petri dish, 0.4 mL of test bacteria liquid (Escherichia coli or Staphylococcus aureus) was dropped onto the surface, a covering film was placed on the petri dish, and the petri dish was covered with a lid. The petri dish was left to stand at 35°C and 90% RH or higher for 24 hours for cultivation. Then, 10 mL of SCDLP medium was added to wash out the test bacteria from the covering film and the test pieces, and the number of bacteria in the washed out solution was measured by the agar plate culture method. The above measurement was performed once for each aluminum fin material, and the average value was taken as the viable bacteria count after cultivation. Test piece 1cm of Reference Example 1 2 The number of viable bacteria after incubation per 1 cm of the test piece of the Example or Comparative Example is Uf. 2 The number of live bacteria after culture per unit area was designated as Af, and the logarithm of Af [log(Uf)-loh(Af)] was calculated as the antibacterial activity value Rf for the corresponding Example or Comparative Example. The results are shown in Table 1, and if the antibacterial activity value is 2.0 or more against at least one of Escherichia coli and Staphylococcus aureus both after water resistance treatment and after light resistance treatment, it can be determined that there is antibacterial effectiveness. In Table 1, "-" means that the measurement was not performed.
[0097] <Hydrophilicity> About 2 μL of ion-exchanged water was dropped onto the fin material surface, and the contact angle of the droplet was measured using a contact angle measuring device (Model CA-05, manufactured by Kyowa Interface Science Co., Ltd.) The contact angle was measured three times for each sample, and the average value was taken as the initial contact angle. Next, the fin material was immersed in a water tank with tap water flowing for 8 hours, and then dried at 80°C for 16 hours, which constituted one cycle. This immersion and drying process was repeated 14 times. After that, the temperature was returned to room temperature, and about 2 μL of ion-exchanged water was dropped onto the fin material surface, and the contact angle of the droplet was measured with a contact angle measuring device (Kyowa Interface Science Co., Ltd.: CA-05 type). The contact angle was measured three times for each sample, and the average value was taken as the contact angle after 14 cycles. The results are shown in "hydrophilicity" in Table 1. If the initial contact angle is 18° or less, it can be evaluated as having good hydrophilicity at least as good as conventional. If the contact angle after 14 cycles is 20°, it can be evaluated as having good hydrophilicity with durability at least as good as conventional. In Table 1, "-" means that the measurement was not performed.
[0098] [Table 1]
[0099] From the results in Table 1, when an organic antiviral / antibacterial agent was contained in the corrosion-resistant film layer as in Comparative Examples 1 to 4, the inherent good hydrophilicity was not obtained even when a hydrophilic film layer was provided, and the degree of decrease in hydrophilicity was also significant. In this case, the antiviral and antibacterial properties after the water-resistant treatment also tended to be inferior.
[0100] In contrast, in Examples 1 and 2, it was found that by incorporating an organic antiviral / antibacterial agent into the hydrophilic coating layer, effective antiviral and antibacterial properties could be achieved while maintaining very good hydrophilicity and its durability. In particular, it was found that antiviral and antibacterial properties could be achieved without compromising the hydrophilic function, even compared to Reference Example 1, which is a conventional aluminum fin material that does not contain an organic antiviral / antibacterial agent. In addition, although the antiviral and antibacterial performance was not evaluated in Example 3, since sufficient antiviral and antibacterial properties were achieved in Example 2, it can be easily assumed that good antiviral and antibacterial properties can also be achieved in Example 3, which contains a higher content of organic antiviral and antibacterial agent than Example 2. On that basis, when the organic antiviral and antibacterial agent is added at 0.75 mg / dm as in Example 3, 2 Even when the organic antiviral / antibacterial agent was included, good hydrophilicity was achieved. However, as the content of the organic antiviral / antibacterial agent was increased, there was a tendency for the appearance of the coating composition for the hydrophilic coating layer to become uneven when it was applied. Therefore, from the viewpoint of forming a homogeneous hydrophilic coating layer by uniformly mixing the organic antiviral / antibacterial agent in the coating composition at a micro level and not excessively impairing the function of the hydrophilic coating layer, the content of the organic antiviral / antibacterial agent was set to a certain value or less, for example, 0.60 mg / dm 2 The following is said to be preferable:
Claims
1. An aluminum plate having a corrosion-resistant coating layer and a hydrophilic coating layer in this order on at least one surface of the aluminum plate; The hydrophilic coating layer of this aluminum fin material contains a hydrophilic resin and an organic antiviral and antibacterial agent.
2. The content of the organic antiviral and antibacterial agent in the hydrophilic coating layer is 0.10 to 0.60 mg / dm 2 The aluminum fin material according to claim 1 .
3. The aluminum fin material according to claim 1 or 2, wherein the organic antiviral / antibacterial agent includes a phenolic antiviral / antibacterial agent.
4. The aluminum fin material according to claim 1 or 2, wherein the hydrophilic resin comprises an acrylic resin containing a sulfonic acid group and an ether bond.
5. The aluminum fin material according to claim 1 or 2, wherein the corrosion-resistant coating layer contains an epoxy resin.
6. The aluminum fin material according to claim 1 or 2, further comprising a lubricating coating layer on a surface of the hydrophilic coating layer.
7. The aluminum fin material according to claim 6, wherein the lubricating coating layer comprises a resin matrix containing polyethylene glycol as a main component and a hydrophilic component containing at least one of a sulfonic acid group and an ester group.
8. The aluminum fin material according to claim 1 or 2, further comprising a base treatment layer between the aluminum plate and the corrosion-resistant coating layer.
Citation Information
Patent Citations
Heat exchanger made of aluminum
JP1992254197A
Aluminum fin material
JP2006078134A
Air conditioner
JP2010203702A
Aluminum fin material
JP2022161706A
Surface treatment method and surface treatment of an aluminum-based substrate base
KR1020170000199A